Influence of AI Technology on the Development of Critical Thinking Skills in Education - Fahmy Syahputra; Elsa Sabrina; Alya Rahmi; Ariyantika Br Ginting; Hanifah Mardhiyah; Hutri Ami; Laili Tanzila (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to the educational process, especially in supporting the development of critical thinking skills in students. This study uses a qualitative approach with a systematic literature review method to analyze various findings regarding the influence of AI in education. The results of the study show that AI has the potential to improve critical thinking skills through the provision of analytical stimuli, adaptive feedback, and the facilitation of active learning that encourages reflection, evaluation, and data-based argumentation. However, excessive use of AI or use without teacher guidance can lead to dependence, reduce creativity, and weaken students' evaluative and independent thinking skills. Therefore, the integration of AI should be balanced with active learning strategies, digital literacy, and pedagogical guidance so that this technology functions as a cognitive partner that strengthens critical thinking processes, rather than as a substitute for students' reasoning.